Characterization of Unsteady Leakage Flow in an Axial Fan - Matteo Dellacasagrande; Edward Canepa; Andrea Cattanei; Mehrdad Moradi (International Journal of Turbomachinery, Propulsion and Power, 2023)
The present work reports an experimental study of the leakage flow in a low-speed fan ring. Existing 2D Particle Image Velocimetry (PIV) measurements taken in a meridional plane in front of the rotor gap have been further processed and analyzed by means of the Proper Orthogonal Decomposition (POD). Three values of the dimensionless pressure rise across the rotor have been investigated. Namely, attention has been focused on the intermediate case—the one for which a strong radial oscillation in the leakage flow has been observed: POD results have shown that, in this condition, the leakage flow exhibits periodic radial oscillations that are not correlated to the periodic blade passing. Moreover, such coherent motions have been found to promote turbulence transport at different radial positions, whereas rotor-related oscillations have a negligible effect in this sense. The present POD procedure can be generally applied to turbomachinery flows to characterize their unsteady behavior beside the classical phase-averaging methods based on rotor-related quantities. The present approach is novel for the study of leakage flow dynamics in axial fans.